2017
DOI: 10.1101/109140
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new model for ancient DNA decay based on paleogenomic meta-analysis

Abstract: Abstract:The persistence of DNA over archaeological and paleontological timescales in diverse environments has led to revolutionary body of paleogenomic research, yet the dynamics of DNA degradation are still poorly understood. We analyzed 185 paleogenomic datasets and compared DNA survival with environmental variables and sample ages. We find cytosine deamination follows a conventional thermal age model, but we find no correlation between DNA fragmentation and sample age over the timespans analyzed, even when… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 58 publications
4
82
0
Order By: Relevance
“…formalin) and those which are much older or ‘ancient’ (e.g. archaeological samples thousands of years old) are likely to present a different set of complications (Kistler, Ware, Smith, Collins, & Allaby, ; McDonough et al, ; Zimmermann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…formalin) and those which are much older or ‘ancient’ (e.g. archaeological samples thousands of years old) are likely to present a different set of complications (Kistler, Ware, Smith, Collins, & Allaby, ; McDonough et al, ; Zimmermann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In Quaternary floras, these affect the transportation, incorporation and preservation of aeDNA in sediments (Birks & Birks, ). For mammal bones, the propensity for tissues and environments to create closed systems appears to be of greater importance than the absolute age of the aeDNA (Kistler, Ware, Smith, Collins, & Allaby, ). To date, there is little knowledge of how taphonomic processes affect the preservation of aeDNA from aquatic habitats, though assemblages derived from aeDNA have been shown to be stable over decadal timescales in lake sediments (Capo, Domaizon, Maier, Debroas, & Bigler, ).…”
Section: Discussionmentioning
confidence: 99%
“…This variation is likely a result of both the age of the specimens and the environmental conditions (temperature, humidity, pH, microorganisms) to which they were exposed since the death of the animal (Sawyer et al, ). Several studies have also demonstrated variation in DNA preservation between archaeological sites and environments (Burger, Hummel, Herrmann, & Henke, ; Kistler, Ware, Smith, Collins, & Allaby, ). The environmental conditions in which fish remains are buried is particularly influential on the extent to which DNA is preserved (Alonso, Häberle, Plogmann, Schibler, & Schlumbaum, ; Speller et al, ).…”
Section: Discussionmentioning
confidence: 99%